Trunk Balance Exercise dan Strength Training Exercise Menurunkan Nyeri Punggung Bawah Pasca 12-18 Bulan Pasca Salin - Andriani Khairunnisa; Roikhatul Jannah (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
Postpartum is a condition at the time of period after delivery from 0 (zero) to sixth weeks, indicated by various musculoskeletal complaints including lower back pain. This pain is related to postural changes after pregnancy, muscle fatigue, and other physiological changes postpartum. Trunk Balance Exercise and Strength Training Exercise are two exercises combined from various references to overcome low back pain consisting of the exercise of postural muscle balance and strengthening of the spinal segment muscles. The purpose of this study was to determine the effect of the combination exercise on lower back pain related to functional ability among the mother 12-18 after delivery. This study uses a pre-experimental design with one group pretest-posttest approach. The intervention was 12 time of 45-60 minutes meeting session during 4 weeks. Respondents were selected by purposive sampling technique. A total of 15 women post 12-18 months of delivery in Posyandu in Cipayung District, East Jakarta participated in this study. The results were obtained by analyzing univariate and bivariate data; normality test data by dividing the value skewness and standard error; and test hypotheses with Paired t-test. This research shows a significant decrease in the Numerical Rating Scale (NRS) with p = 0.00 <0.05. Conclusion: Trunk Balance Exercise and Strength Training Exercise have an effect against low back pain associated with functional ability in post-12-18 mothers.